Complex Roots of a Quadratic Equation

We will discuss about the complex roots of a quadratic equation.

In a quadratic equation with real coefficients has a complex root α + iβ then it has also the conjugate complex root α - iβ.

Proof:

To prove the above theorem let us consider the quadratic equation of the general form:

ax\(^{2}\) + bx + c = 0 where, the coefficients a, b and c are real.

Let α + iβ (α, β are real and i = √-1) be a complex root of equation ax\(^{2}\) + bx + c = 0. Then the equation ax\(^{2}\) + bx + c = 0 must be satisfied by x = α + iβ.

Therefore,

a(α + iβ)\(^{2}\) + b(α + iβ) + c = 0

or, a(α\(^{2}\) - β\(^{2}\) + i 2 αβ) + bα + ibβ + c = 0, (Since, i\(^{2}\) = -1)

or, aα\(^{2}\) - aβ\(^{2}\) + 2iaαβ + bα + ibβ + c = 0,

or, aα\(^{2}\) - aβ\(^{2}\) + bα + c + i(2aαβ + bβ) = 0,

Therefore,

aα\(^{2}\) - aβ\(^{2}\) + bα + c = 0 and 2aαβ + bβ = 0

Since, p + iq = 0 (p, q are real and i = √-1) implies p = 0 and q = 0]

Now substitute x by α - iβ in ax\(^{2}\) + bx + c we get,

a(α - iβ)\(^{2}\) + b(α - iβ) + c

= a(α\(^{2}\) - β\(^{2}\) - i 2 αβ) + bα - ibβ + c, (Since, i\(^{2}\) = -1)

= aα\(^{2}\) - aβ\(^{2}\) - 2iaαβ + bα - ibβ + c,

= aα\(^{2}\) - aβ\(^{2}\) + bα + c - i(2aαβ + bβ)

= 0 - i 0 [Since, aα\(^{2}\) - aβ\(^{2}\) + bα + c = 0 and 2aαβ + bβ = 0]

= 0

Now we clearly see that the equation ax\(^{2}\) + bx + c = 0 is satisfied by x = (α - iβ) when (α + iβ) is a root of the equation. Therefore, (α - iβ) is the other complex root of the equation ax\(^{2}\) + bx + c = 0.

Similarly, if (α - iβ) is a complex root of equation ax\(^{2}\) + bx + c = 0 then we can easily proved that its other complex root is (α + iβ).

Thus, (α + iβ) and (α - iβ) are conjugate complex roots. Therefore, in a quadratic equation complex or imaginary roots occur in conjugate pairs.

 

Solved example to find the imaginary roots occur in conjugate pairs of a quadratic equation:

Find the quadratic equation with real coefficients which has 3 - 2i as a root (i = √-1).

Solution:

According to the problem, coefficients of the required quadratic equation are real and its one root is 3 - 2i. Hence, the other root of the required equation is 3 - 2i (Since, the complex roots always occur in pairs, so other root is 3 + 2i.

Now, the sum of the roots of the required equation = 3 - 2i + 3 + 2i = 6

And, product of the roots = (3 + 2i)(3 - 2i) = 3\(^{2}\) - (2i)\(^{2}\) = 9 - 4i\(^{2}\) = 9 -4(-1) = 9 + 4 = 13

Hence, the equation is

x\(^{2}\) - (Sum of the roots)x + product of the roots = 0

i.e., x\(^{2}\) - 6x + 13 = 0

Therefore, the required equation is x\(^{2}\) - 6x + 13 = 0.





11 and 12 Grade Math 

From Complex Roots of a Quadratic Equation to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.